Approximating the Asset Pricing Kernel - CHAPMAN, DAVID A. (Journal of Finance, 1997)
ABSTRACT This article tests a simple consumption‐based asset pricing model by approximating the true asset pricing kernel using low‐order orthonormal polynomials based on the model's state variables. Approximated kernels based solely on next period's consumption growth are not rejected by overall measures of model fit, but they produce statistically and economically large pricing errors. Approximated kernels based on two quarters of future consumption growth and technology shocks have substantially improved overall fit. In particular, the best of these kernels are capable of eliminating the small firm effect.